UJI AKTIVITAS ANTIOKSIDAN DAN PENAPISAN FITOKIMIA DARI EKSTRAK DAUN PAKOASI DAN KLUWIH SEBAGAI SUMBER ANTIOKSIDAN ALAMI - Nurlaila Agustikawati; Yayuk Andayani; Dedy Suhendra (Jurnal Penelitian Pendidikan IPA, 2017)
This study aims to determine the antioxidant activity and secondary metabolism of pakoasi leaf extract and kluwih leaf. Analysis using DDPH method (1,1-diphenyl-2-picrylhydrazyl). Result of antioxidant activity test in. Concentration Barriers (IC50). IC50 values for leaf extract of pakoasi and kluwih leaves were 89.659 μg / mL and 54.719 μg / mL greater than IC50 vitamin C of 46.74 μg / mL. Qualitative analysis of antioxidant compounds using TLC technique showed seven chromatogram profiles for pakoasi leaf extract and four chromatogram profiles for kluwih leaf extract. In addition, phytochemical analysis of leaf extract of pakoasi and kluwih leaves showed the presence of saponin compounds, tannins, phenols, flavonoids, steroids and triterpenoids. Based on the results of this analysis concluded that leaf extract of pakoasi and kluwih leaf as natural source of antioxidant which can be seen with IC50 value in the sample is in strong category and supported from phytolyte analysis result which according to phenol and flavonoid which act as antioxidant.Keywords: Antioxidant activity, phytochemical analysis ethanol extract, green bean leaves, kluwih leaves, leaves of pakoasi